Digitalization of Islamic Educational Materials in Forming Islamic Generation Z Character - Umi Masluhah (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2022)
The increasingly important use of digital technology influences the world of education, especially generation Z, who are referred to as digital natives, meaning that the internet has become a part of life because the internet has surrounded them from the womb to the beginning of birth. This research is qualitative research with a descriptive method of analysis, which will examine the digitalization of learning materials using conventional book media combined with video barcode scans. Later, the learning material will become more interesting so that students can understand the message or material conveyed in the video above. This research that the author can conclude is that the digitalization of Islamic Religious Education material at SDI AR Roudhoh is to collaborate learning materials in conventional media packaged in the form of LKS books with digital learning media in the form of sparkol videos or vidioscribes that are broadcast on television or smartphones, and with this learning media students have a high interest in understanding the learning material using the media. So that students can understand the learning material well and apply the value of Islamic education in everyday life.